Applications of Ionic Liquids in Science and Technology - Handy, Scott (IntechOpen, 2011)
This volume of the two volume set on ionic liquids focuses on the applications of ionic liquids in a growing range of areas. Throughout the 1990's, it seemed that most of the attention in the area of ionic liquids applications was directed toward their use as solvents for organic and transition-metal-catalyzed reactions. Certainly this interest continues on to the present date, but the most innovative uses of ionic liquids span a much more diverse field than just synthesis. Some main topics of coverage include the application of RTILs in various electronic applications (batteries, capacitors, and light emitting materials), polymers (synthesis and functionalization), nanomaterials (synthesis and stabilization), and separations. More unusual applications can be noted in the fields of biomass utilization, spectroscopy, optics, lubricants, fuels, and refrigerants. It is hoped that this diversity of this volume will serve as an inspiration for even further advances in the use of RTILs.